(3CYJGH GdcJGHs - (3eMeO Hf YHO Gddg Hf CHj HcQ GdbVGYj GdHdfSj, CHh YHO Gddg, GHf GdnCnqHGQ,J (B658 (3g` s
(3ChdgG (B:s
(3CeG HYO MeO Gddg GdPj jYah Yf GdSjFGJ, hGdUdGI Ydi eMeO QShd Gddg GdNGU HSjGOI cd eGV hBJ agPg ofHPI ef CYJGH GdcJGH hJUfjY GdBOGH hJTgO HeG dge YfO GdCeQGA hGdNdaGA s
(3BNQgG (B:s
(3JTaYJ ajgG ddEeGe HfLdg hfYe TajY GdeDefjf eMeO fLRJ GdQSGdI GdehSheI HCYJGH GdcJGH GdeYQha HGHf GdCHGQ s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B233 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B10 - (3U (B204s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B97 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B33 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs